Natural Resource Management in the Thar Desert Region of Rajasthan - Varghese, Nisha; Burark, Sukhdeo Singh; Varghese, K.A. (Cham : Springer International Publishing : Imprint: Springer, 2023)
This book covers a wide range of issues related to the Thar Desert Region of Rajasthan from an integrated and sustainable development perspective. The chapters in this book cover regional and local issues which are discussed with reference to the past scenario, the present practices, and the future strategies. Some of the issues addressed in this book like arid agroforestry, livelihood, and multidimensional development give it a cutting edge over other related publications currently available in the market. The chapters are supported with relevant pictures which will help the reader to connect with the issues being discussed. This book is useful to students, civil services aspirants, researchers, environmentalists, geographers, and non-professionals who are interested in deserts and desert development.
An Overview of World Deserts with Special Reference to Thar Desert -- People and Culture of the Thar Desert -- Shift in Land Use Pattern of Thar Desert -- Land and Water Resource Management in the Thar Desert Region -- Crop Production Practices in the Thar Desert Region of Rajasthan -- Livestock and its Management Practices in Thar Desert, Rajasthan -- Arid Agroforestry for Thar Desert -- Soil Conservation and Water Harvesting for Sustainable Agriculture in Arid Regions -- Community Land Management in the Thar Desert -- Women Empowerment in Thar Desert Region -- Livelihood Opportunities in the Thar Region -- Potential Agri-Business in the Thar Desert -- Multidimensional Development in Thar Desert Region of Rajasthan -- Sustainable Natural Resource Management in Thar Desert-Way Ahead. .
Keywords: Geology; Human ecology -- Study and teaching; Environment; Environmental management; Geology; Environmental Studies; Environmental Sciences; Environmental Management